Factors influencing decision making among ENT surgeons on performance of cortical mastoidectomy for CSOM-tubotympanic disease in quiescent/active stage: an opinion based study - Gayathri, H.; Balachandran, Krishnamurthy; Rathnasamy, Ponnan; Paul, Christina Mary (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: As the role of cortical mastoidectomy as an adjunct to tympanoplasty in the management of CSOM tubotympanic type - quiescent stage remains controversial even today; we intend to study the factors that influence the decision of ENT surgeons on whether or not to perform cortical mastoidectomy in patients with CSOM (chronic suppurative otitis media) - active or quiescent ear. Methods: During May to August 2016, 60 ENT surgeons within Chennai were asked to answer a pre-framed questionnaire on CSOM based on their personal surgical experience. The answers were collected by direct questionnaire method and the data subjected to appropriate statistical analysis. Results: 65% surgeons expected a minimum dry ear period of ≤30 days before considering tympanoplasty alone (group 1) and the rest 35% members expected more than 30 days of dry ear period (group 2). Surgeons ≤40 years of age expected lesser duration of dry ear period prior to consideration of tympanoplasty alone (p =0.016). Group 2 surgeons performed cortical mastoidectomy in more number of cases (>50%) when compared to group 1 surgeons (p =0.03) for patients who presented first to them with a wet ear. There was a mixed opinion among surgeons within group 1 itself on whether or not they would do cortical mastoidectomy when they encountered patients who had congested remnant tympanic membrane, congested middle ear mucosa, myringosclerosis, ossicular chain discontinuity, sclerotic mastoids or treated septic foci in spite of the ear being dry for a month. Conclusions: Though many surgeons consider that 30 days of dry ear period is sufficient to consider tympanoplasty alone, there is a division of opinion among themselves while facing specific clinical scenarios.